Ammonia reduction by different thickness coral shard filter in cultivation of Catfish (Pangasius sp) - Desi Maria Sabu; Ade Yulita Hesti Lukas; Yuliana Salosso (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
Catfish (Pangasius sp.) is a consumption fish that is quite popular and has a selling value. Fish have tolerance standards for water quantity and quality, so water as a living medium should be managed in aquaculture. One of the water quality parameters that affect the survival of cultured fish is ammonia (NH₃). Ammonia at high concentrations can adversely affect fish, such as reducing the ability of the blood to carry oxygen, damage to body tissues, fish susceptible to disease, inhibiting growth and death. This research aimed to determine the thickness of the coral shard filter, which effectively reduces ammonia (NH₃) in catfish culture. This research was conducted at the Dry Fisheries Laboratory, Faculty of Animal Husbandry, Fisheries and Marine Science, University of Nusa Cendana. The research started from February 2022 - April 2022. The implementation of this research used a Completely Randomized Design (CRD) with 4 treatments and 3 replications, namely: without coral shards filter (A), treatment using a coral shard filter with a thickness of 5 cm (B), coral shard filter with a thickness of 10 cm (C) and coral shard filter with a thickness of 15 cm (D). Results show that filter coral shards treatment with 5 cm thickness can reduce the concentration of ammonia in the cultivation of fish catfish from a score beginning research of 0.02 mg/L to 0.018 mg/L in the end research.